Intermodal Brillouin scattering in solid-core photonic crystal fibers - Jarschel, Paulo F.; Lamilla, Erick; Espinel, Yovanny A. V.; Aldaya, Ivan [UNESP]; Pita, Julian L.; Gil-Molina, Andres; Wiederhecker, Gustavo S.; Dainese, Paulo (Amer Inst Physics, 2021)
We investigate intermodal forward Brillouin scattering in a solid-core photonic crystal fiber (PCF), demonstrating efficient power conversion between the HE11 and HE21 modes, with a maximum gain coefficient of 21.4 W-1 km(-1). By exploring mechanical modes of different symmetries, we observe both polarization-dependent and polarization-independent intermodal Brillouin interaction. Finally, we discuss the role of squeeze film air damping and leakage mechanisms, ultimately critical to the engineering of PCF structures with enhanced interaction between high-order optical modes through flexural mechanical modes.